Structural Shifts in the English-Indonesian Novel Translation: A Systemic Functional Linguistics Analysis - Nurul Ariefyanti (Universitas Pendidikan Indonesia (UPI), 2018)
This study aims to analyze types of structural shifts found in the nominal groups and verbal groups a novel translation and investigate how the structural shifts affect the meaning. This study follows a descriptive qualitative method (see Cresswell (2009). The data of the study are taken from the novel entitled “The Fault in Our Stars” by Green (2012) and the Indonesian version translated by Nimpoeno (2016). The analysis of the study draws on Gerot and Wignell’s (1994) theory of nominal group and transitivity and Catford’s (1965) translation theory as the basis of the categorization of the structural shifts. The data analysis reveals that there are two types of structural shifts found in the data. Those are single translation shift that includes: 1) structure shift, 2) unit shift, 3) class shift, and 4) intra-system shift and double translation shift that is the combination of the shifts. The study shows that the most frequent shifts found in the structural shifts of nominal groups is the combination of structure and class shift (38.94%). On the contrary, the most frequent shift found in the verbal groups is intra-system shift (70.59%) which belongs to the single translation shift. The study shows that structural shifts slightly affect meanings of the translation. This study suggests that linguistic analysis can indicate how learning to translate requires linguistics knowledge of certain language as the expert translators conduct the translation. Keywords: structural shifts, nominal group, verbal group, meaning shift, novel translation